Metformin inhibits RANKL and sensitizes cancer stem cells to denosumab. Issue 11 (3rd June 2017) - Cuyàs, Elisabet; Martin-Castillo, Begoña; Bosch-Barrera, Joaquim; Menendez, Javier A.
ABSTRACT: The increased propensity of BRCA1 mutation carriers to develop aggressive breast tumors with stem-like properties begins to be understood in terms of osteoprotegerin (OPG)-unrestricted cross-talk between RANKL-overproducing progesterone-sensor cells and cancer-initiating RANK + responder cells that reside within pre-malignant BRCA1 mut/+ breast epithelial tissue. We recently proposed that, in the absence of hormone influence, cancer-initiating cells might remain responsive to RANKL stimulation, and hence to the therapeutic effects of the anti-RANKL antibody denosumab because genomic instability induced by BRCA1 haploinsufficiency might suffice to cell-autonomously hyperactivate RANKL gene expression. Here we report that the biguanide metformin prevents BRCA1 haploinsufficiency-driven RANKL gene overexpression, thereby disrupting an auto-regulatory feedback control of RANKL-addicted cancer stem cell-like states within BRCA1 mut/− cell populations. Moreover, metformin treatment elicits a synergistic decline in the breast cancer-initiating cell population and its self-renewal capacity in BRCA1 -mutated basal-like breast cancer cells with bone metastasis-initiation capacity that exhibit primary resistance to denosumab in mammosphere assays. The specific targeting of RANKL/RANK signaling with denosumab is expected to revolutionize prevention and treatment strategies currently available for BRCA1 mutation carriers. Our findings provide a rationale for new denosumab/metformin combinatorial strategies to clinically manage RANKL-related breast oncogenesis and metastatic progression.